2000
DOI: 10.1542/peds.106.6.e86
|View full text |Cite
|
Sign up to set email alerts
|

Circumstances Leading to a Change to Prone Sleeping in Sudden Infant Death Syndrome Victims

Abstract: ABSTRACT.Context. In addition to usual prone sleeping, unaccustomed prone sleeping represents a significant risk factor for sudden infant death syndrome (SIDS). However, little information is available regarding the circumstances leading caretakers to change the infant's sleep position to prone position in SIDS victims.Objective. To determine, in a population of SIDS victims, the timing of a change to prone sleeping and the reason for that change in infants who were originally nonprone sleepers.Design and Sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2004
2004
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…1,3,20 Certainly, the present findings support this concept. These same findings indicate, however, that even with substantial pronesleep experience, some infants are still unable to protect their airway fully.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…1,3,20 Certainly, the present findings support this concept. These same findings indicate, however, that even with substantial pronesleep experience, some infants are still unable to protect their airway fully.…”
supporting
confidence: 84%
“…[1][2][3] That is to say, SIDS risk is greatly increased over that of infants who are used to sleeping prone. Furthermore, when SIDS infants who are inexperienced in prone sleep are found lying prone at death, they are more likely to be found face down than infants who are used to prone sleep.…”
mentioning
confidence: 99%
“…As all infants routinely slept supine at home, infants in our study were ‘naïve’ prone sleepers at the time of each study. It has been suggested that infants who are inexperienced in prone sleeping are at increased risk of SIDS if they are placed prone (Cote et al. , 2000; Paluszynska et al.…”
Section: Discussionmentioning
confidence: 99%
“…Many parents change the infant's sleep position at 2 to 4 months (when the infant is at highest risk for SIDS), often because of concerns about sleep quality and infant comfort. 40,41 Changing the position from supine to prone places the infant at extremely high risk for SIDS. 42,43 It is therefore important for physicians to address the infant's sleep environment at every wellchild visit for the first year of life, especially in the first 6 months, the age by which most SIDS deaths occur.…”
Section: Discussionmentioning
confidence: 99%